Digital Marketing Model for Sustainable Ecotourism Development in Kerinci Regency - Anggia Ayu Lestari; Melifia Liantifa (Economics and Digital Business Review, 2026)
Study This discuss implementation of digital marketing models in sustainable digital ecotourism development in the Regency Kerinci . Digital transformation in sector tourist demand the existence of a better marketing strategy adaptive , data -driven , and sustainability - oriented environment as well as social research This aim For analyze effectiveness digital marketing in increase visibility and power pull destination tour nature in the Regency Kerinci . The research method used is a mixed method with approach quantitative and qualitative . Quantitative data obtained through survey to tourists and actors tourism , while qualitative data collected through interview deep with stakeholders interest tourist local . Research results show that digital marketing through social media , destination websites , and visual content contributes significant to improvement visit tourism . In addition , integration mark ecotourism in digital marketing strategy to strengthen image destination sustainable research This recommend optimization of digital content strategies based on storytelling and strengthening collaboration between government area , perpetrator tourism and community local .